2017
DOI: 10.1093/bjsw/bcx042
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-Training Characteristics of Frontline Participants and Mainstream Social Work Students

Abstract: Frontline is a fast-track training scheme for social workers in children's services in England, which aims to attract 'outstanding' graduates who may not previously have considered a career in social work. This implies that students recruited onto the Frontline programme will be of a higher academic quality than those on mainstream social work courses. This article presents findings from an independent evaluation of the Frontline pilot stage which compared the pre-training characteristics of Frontline particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Maxwell et al (2016) found that 59% of the first Frontline cohort had a parent with a degree, compared to 31% of the wider student cohort. These class disparities have been consistently maintained, and in a later evaluation of Frontline it was found that participants were more likely to have gone to private school and to have a parent who is a university graduate (Maxwell et al, 2018). Furthermore, there are concerns related to the condensed nature of these fast-track programmes, and the implications for diversity that this creates.…”
Section: Widening Participation and Social Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Maxwell et al (2016) found that 59% of the first Frontline cohort had a parent with a degree, compared to 31% of the wider student cohort. These class disparities have been consistently maintained, and in a later evaluation of Frontline it was found that participants were more likely to have gone to private school and to have a parent who is a university graduate (Maxwell et al, 2018). Furthermore, there are concerns related to the condensed nature of these fast-track programmes, and the implications for diversity that this creates.…”
Section: Widening Participation and Social Workmentioning
confidence: 99%
“…Concerns related to the lack of diversity on fast-track programmes were raised in early evaluations, and have continued to be a concerning feature as these programmes have expanded (Smith et al, 2013;Maxwell et al, 2016;Maxwell et al, 2018). For example, postgraduate social work education overall has 38% Black, Asian and Minority Ethnic (BAME) students (Skills for Care, 2018), compared to recent cohorts of Think Ahead and Frontline who had 16% and 18% respectively (Think Ahead, 2017; Frontline, 2018b).…”
Section: Widening Participation and Social Workmentioning
confidence: 99%
See 2 more Smart Citations
“…SUAC involvement in the qualifying training of social workers became mandatory in 2002 (Department of Health 2002). However, the extent to which universities providing professional social work training have embraced the involvement of SUACs in meaningful ways is open to debate and recent 'fast track' field-based social work training initiatives such as 'Frontline' (Maxwell et al 2016) and 'Think Ahead' (Clifton and Thorley 2014) have paid scant attention to the SUAC voice. The potential to embed the SUAC voice from the beginning of professional training can underline to students that the people with whom they work are human beings first and foremost, and also provides opportunities for SUACs to flourish and develop skills in a learning and teaching environment not previously available to them.…”
Section: The Changing Environment Of Health Care and Social Workmentioning
confidence: 99%